Hydrodynamic response and tendon mechanics of tension-leg platform floating offshore wind turbines: A critical review and future perspectives - Haozhe Bai; Sami Ur Rehman; Abid Ali; Muhammad Irslan Khalid; Wei Shi; Fengmei Jing; Sajid Ali; Muhammad Asghar; Sheraz Hussain; Chunlei He (Ocean Engineering, 2026)

Spatially resolved estimates of phytoplankton carbon fixation and diffusive methane flux potential in a subtropical reservoir - Sheraz Akhtar Gil; YuPing Su; Gohar Ayub; Abdul Samad; Muhammad Irfan Ahamad; Jehangir Ijaz; Shiyu Huang; Weng Yuxin (Environmental Monitoring and Assessment, 2026)

An overview of smart windows in Passivhaus design for enhanced energy efficiency and comfort in net-zero buildings - Alejandro Moreno-Rangel; Muhammad Norhaffis Mustafa; Muhammad Sheraz Ahmad; Arshid Numan; Mohammad Khalid (Innovative Infrastructure Solutions, 2026)

Multi-index remote sensing and GIS-based assessment of Shisper Glacier surge dynamics and glacial lake outburst flood hazard in Hunza, Pakistan - Maida Khanum; Yuping Su; Shakeel Mahmood; Kanwal Javid; Jehangir Ijaz; Sheraz Akhtar Gil; Muhammad Irfan Ahamad; Rana Muhammad Zulqarnain (Environmental Monitoring and Assessment, 2026)

A novel spatiotemporal and machine learning framework for sustainable groundwater monitoring and management - Sheraz Maqbool; Muhammad Imran Khan; Aamir Raza; Mumtaz Ali; Naeem Saddique; Qaisar Saddique (Groundwater for Sustainable Development, 2026)

Retraction Note: Adenosine protects D-galactose induced alterations in rat model of aging via attenuating neurochemical profile and redox status - Noreen Samad; Arooj Nasir; Muhammad Habib ur Rehman; Sheraz Ahmed Bhatti; Imran Imran (Metabolic Brain Disease, 2026)

Fe-Ce interaction-driven active site modulation in a porous MOF for oxygen evolution reaction - Sheraz Muhammad; Lixia Wang; Mingcheng Gao; Sumayya Khan; Wentao Xu; Asif Ali; Tayirjan Taylor Isimjan; Shohreh Azizi; Xiulin Yang (Fuel, 2026)

Jinggangmycin-induced NlPR-L and NlABD4-L genes regulate fecundity in the brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) - Sheraz Ahmad; Muhammad Zubair; Zhirou Duan; Zhiyue Mao; Xinyu Tang; Xudong Zhao; Linquan Ge (Pesticide Biochemistry and Physiology, 2025)

Wooden ash based nylon fiber reinforced concrete: experimental study on concrete strength properties - Muhammad Sheraz; Qiang Yuan; Muhammad Alam; Muhammad Faisal Javed (Innovative Infrastructure Solutions, 2025)

Exploring nonstructural NS5B protein to design a multi-epitope-based vaccine against HCV: immuno-informatics approach - Nouman Ali; Adeeba Ali; Muhammad Sheraz Yousuf; Arsheen Rehman; Saad Muhammad Islam; Bilal Ilyas; Aamir Ali (In Silico Pharmacology, 2025)

Enhanced electrochemical nitrate reduction: Geometrically tailored Pd/Cu electrodes for superior nitrogen selectivity - Thi Nhat-Tuyen Nguyen; Kiruthika Mariappan; Muhammad Sheraz Ahmad; Feng-Ze Tian; Ching-Wei Tung; Jenn Fang Su; Chao-Lin Liu; Ching-Lung Chen (Journal of Environmental Chemical Engineering, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

MnFe2O4 thin film electrodes via AACVD: A facile route for enhanced oxygen evolution reaction - Alishbah Zaka; Misha Aftab; Nudrat Fatima; Khola Mashood; Muhammad Adeel Asghar; Arshid Numan; Muhammad Sheraz Ahmad; Ali Haider; Mudassir Iqbal; Waqas Ali Shah; Muhammad Adil Mansoor (Fuel, 2025)

Petrographic and geochemical analysis to predict the depositional setting of middle Eocene Jatta Gypsum, Kohat Sub-Basin, Pakistan - Noman Khan; Muhammad Kashif; Arzish Ithaf; Sheraz Habib; Hassanat Ullah; Khalid Ali Khan (Carbonates and Evaporites, 2025)

Carbon nanotubes oriented bifunctional electrocatalyst supported on flexible material for overall water splitting - Alizah Jabeen; Ahmed M. Fallatah; Tahani Rahil Aldhafeeri; A. Alhadhrami; Abdulraheem SA Almalki; Sheraz Yousaf; Zeinhom M. El-Bahy; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2025)

Advances in CO2 hydrogenation: Mechanisms and catalysts for alcohol synthesis - Muhammad Kashif Khan; Sheraz Ahmed; Syeda Sidra Bibi; Ahmad Helaley; Xinhua Liang; Jaehoon Kim (Chemical Engineering Journal, 2025)

Advanced characterization of hemp biomass pyrolysis: Bioenergy recovery and environmental implications - Rashid Minhas; Asif Hussain Khoja; Hajirah Kanwal; Muhammad Hassan; Arslan Khan; Syed Sheraz Daood; Israf Ud din; Ali Bahadar (Sustainable Chemistry and Pharmacy, 2025)

Human Microbiome and Bacteriophages: Impacts on Health and Disease - Muhammad Sheraz; Hongyan Shi; Santasree Banerjee (Current Clinical Microbiology Reports, 2025)

Geospatial assessment of climate variability and drought patterns: a case study from Pakistan - Sher Shah Hassan; Muhammad Arif Goheer; Humera Farah; Faiza Hafeez; Khurram Sheraz; Javaria Fahad; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Multiferroic Y Sn co-doped BiFeO3 2D nanoplates for enhanced photocatalytic degradation of cationic dyes: Synthesis, chemistry and mechanisms - Ahmad Umair; Mirza Mahmood Baig; Sheraz Yousaf; Muhammad Touqeer; Mehboob Hassan; Ali Ahmad; Joon Kim; Hyuntae Ju; Seung Goo Lee (Journal of Water Process Engineering, 2025)

Monitoring and biochemical characterization of resistance against commonly used insecticides in cotton jassid, Amrasca biguttula (Ishida) from Punjab, Pakistan - Sikandar Hussain; Shoaib Freed; Afifa Naeem; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Muhammad Waqas Sumra (International Journal of Tropical Insect Science, 2025)

MXenes: Transforming advanced materials through electrochemical reduction reactions – Opportunities and challenges - Tahir Rasheed; Sameera Shafi; Muhammad Tuoqeer Anwar; Rabia Ahmad; Muhammad Sheraz Ahmad; Muhammad Usman; Khaled Fahmi Fawy (Chemical Engineering Journal, 2025)

Potential of iron oxide-modified biochar in simultaneous mitigation of lead and nickel toxicity in wheat (Triticum aestivum L.) - Tufail Shah; Muhammad Kashif Irshad; Wasim Javed; Mahshab Sheraz; Atif Muhmood; Ali Noman; Maryam M. Alomran; Sang Soo Lee; Jianying Shang (South African Journal of Botany, 2024)

Candle soot-modified rPET electrospun nanofibrous membrane for separating on-demand oil-water mixture and emulsions - Panchan Dansawad; Lixia Cao; Shengyong Zhao; Haigang Gao; Muhammad Sheraz; Cong Xue; Yanxiang Li; Wangliang Li (Journal of Environmental Chemical Engineering, 2024)

Successful application of modified crude DNA extraction from muscle tissues for various types of PCR amplifications - Sana Jafar; Salman Jamil; Muhammad Sheraz Yasin; Asif Naseem; Muhammad Yasir Zahoor; Wasim Shehzad; Muhammad Imran (Molecular Biology Reports, 2024)

Effect of green synthesized silver nanoparticles on growth and physiological responses of pearl millet under salinity stress - Zakir Ullah; Syed Inzimam Ul Haq; Abd Ullah; Muhammad Ahsan Asghar; Mahmoud F. Seleiman; Khansa Saleem; Fanjiang Zeng; Noor Us Sama; Khalid Kamran; Sheraz Ahmad (Environment, Development and Sustainability, 2024)

Dietary Chlorella vulgaris mitigates aflatoxin B1 toxicity in broiler chicken: Toxicopathological, hematobiochemical and immunological perspectives - Aisha Khatoon; Aneela Amin; Sana Majeed; Shafia Tehseen Gul; Muhammad Imran Arshad; Muhammad Kashif Saleemi; Ashiq Ali; Rao Zahid Abbas; Sheraz Ahmad Bhatti (Toxicon, 2024)

Energy transition in OECD countries: Catalyzing governance quality for SDG 7 attainment - Muhammad Sheraz; Quande Qin; Muhammad Zubair Mumtaz (Energy Policy, 2024)

Structure-activity relationship and deactivation behavior of iron oxide during CO2 hydrogenation - Sheraz Ahmed; Wonjoong Yoon; Heuntae Jo; Muhammad Irshad; Muhammad Kashif Khan; Jaehoon Kim (Chemical Engineering Journal, 2024)

Aflatoxin B1-associated oxidative stress along with toxicopathological and immunological alterations is efficiently counteracted by dietary supplementation of distillery yeast sludge in broilers - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Muhammad Kashif Saleemi; Halis Oguz; Shafia Tehseen Gul; Rao Zahid Abbas; Ashiq Ali; Sheraz Ahmad Bhatti (Mycotoxin Research, 2024)

Moving toward sustainable goals 7 and 13: An inclusive mechanism to achieve environmental sustainability through digitalization and energy transition in OECD countries - Muhammad Sheraz; Quande Qin; Muhammad Zubair Mumtaz; Mushtaq Hussain Khan (Journal of Environmental Management, 2024)

A comprehensive review on the enantiomeric separation of chiral drugs using metal-organic frameworks - Anees Abbas; Muhammad Sheraz Ahmad; Yu-Hsiang Cheng; S. AlFaify; Soohoon Choi; Rana Muhammad Irfan; Arshid Numan; Mohammad Khalid (Chemosphere, 2024)

A holistic overview of the in-situ and ex-situ carbon mineralization: Methods, mechanisms, and technical challenges - Farzain Ud Din Kirmani; Arshad Raza; Sheraz Ahmad; Muhammad Arif; Mohamed Mahmoud (Science of The Total Environment, 2024)

Role of alkali metal in maintaining iron integrity during direct CO2 hydrogenation - Wonjoong Yoon; Heuntae Jo; Sheraz Ahmed; Muhammad Kashif Khan; Muhammad Irshad; Jiyeon Lee; Syeda Sidra Bibi; Jaehoon Kim (Chemical Engineering Journal, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

Corrigendum to “Electrochemical nitrate reduction over bimetallic Pd–Sn nanocatalysts with tunable selectivity toward benign nitrogen” [350 (2024) 141182] - Jenn Fang Su; Muhammad Sheraz Ahmad; Wei-Fan Kuan; Ching-Lung Chen; Tahir Rasheed (Chemosphere, 2024)

Electrochemical nitrate reduction over bimetallic Pd–Sn nanocatalysts with tunable selectivity toward benign nitrogen - Jenn Fang Su; Muhammad Sheraz Ahmad; Wei-Fan Kuan; Ching-Lung Chen; Tahir Rasheed (Chemosphere, 2024)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Underground geological sequestration of carbon dioxide (CO2) and its effect on possible enhanced gas and oil recovery in a fractured reservoir of Eastern Potwar Basin, Pakistan - Anaiz Gul Fareed; Asif Hussain Khoja; Fabio De Felice; Antonella Petrillo; Muhammad Arsalan Sultan; Zafar Khan Jalalzai; Syed Sheraz Daood (Science of The Total Environment, 2023)

Policies and regulations for solar photovoltaic end-of-life waste management: Insights from China and the USA - Amjad Ali; Sheraz Alam Malik; Md Shafiullah; Muhammad Zeeshan Malik; Md Hasan Zahir (Chemosphere, 2023)

3D cellular lattice like-Ti3C2 MXene based aerogels embedded with metal selenides particles for energy storage and water splitting applications - Khadija Chaudhary; Beriham Basha; Sonia Zulfiqar; Sheraz Yousaf; Eric W. Cochran; M.S. Al-Buriahi; Muhammad Farooq Warsi; Muhammad Shahid (Fuel, 2023)

Recent advances in green hydrogen production, storage and commercial-scale use via catalytic ammonia cracking - Muhammad Asif; Syeda Sidra Bibi; Sheraz Ahmed; Muhammad Irshad; Muhammad Shakir Hussain; Hassan Zeb; Muhammad Kashif Khan; Jaehoon Kim (Chemical Engineering Journal, 2023)

Visible light-driven photocatalytic bacterial inactivation on PPE, supported by the DFT and bactericidal study - Gulzar Ahmed; Adeel Rasheed; Khurram Shahzad Munawar; Satesh Bandaru; Javid Khan; Zhongwu Liu; Muhammad Sheraz Ahmad (Environmental Science and Pollution Research, 2023)

Enhanced nitrate reduction over functionalized Pd/Cu electrode with tunable conversion to nitrogen and sodium hydroxide recovery - Kuan-Ling Chen; Muhammad Sheraz Ahmad; Ching-Lung Chen (Science of The Total Environment, 2023)

Nitrogen-phosphorous co-doped palladium electrocatalyst for glycerol electro-oxidation reaction (GEOR): An efficient system for mesoxalic acid and dihydroxyacetone production - Muhammad Sheraz Ahmad; Kim Hoong Ng; Ching-Lung Chen; Faryal Kabir; Thongthai Witoon; Ta Yeong Wu; Chin Kui Cheng (Fuel, 2023)

Correction to: Quantifying the effect of waste on soil health in European Union: what are the roles of technology, natural capital, and institutional quality? - Muhammad Ibrahim Shah; Abdulrasheed Zakari; Siddharth Kumar; Shujaat Abbas; Muhammad Sheraz (Environmental Science and Pollution Research, 2023)

BoT-Net: a lightweight bag of tricks-based neural network for efficient LncRNA–miRNA interaction prediction - Muhammad Nabeel Asim; Muhammad Ali Ibrahim; Christoph Zehe; Johan Trygg; Andreas Dengel; Sheraz Ahmed (Interdisciplinary Sciences: Computational Life Sciences, 2022)
Background and objective: Interactions of long non-coding ribonucleic acids (lncRNAs) with micro-ribonucleic acids (miRNAs) play an essential role in gene regulation, cellular metabolic, and pathological processes. Existing purely sequence based computational approaches lack robustness and efficiency mainly due to the high length variability of lncRNA sequences. Hence, the prime focus of the current study is to find optimal length trade-offs between highly flexible length lncRNA sequences. Method The paper at hand performs in-depth exploration of diverse copy padding, sequence truncation approaches, and presents a novel idea of utilizing only subregions of lncRNA sequences to generate fixed-length lncRNA sequences. Furthermore, it presents a novel bag of tricks-based deep learning approach “Bot-Net” which leverages a single layer long-short-term memory network regularized through DropConnect to capture higher order residue dependencies, pooling to retain most salient features, normalization to prevent exploding and vanishing gradient issues, learning rate decay, and dropout to regularize precise neural network for lncRNA–miRNA interaction prediction. Results BoT-Net outperforms the state-of-the-art lncRNA–miRNA interaction prediction approach by 2%, 8%, and 4% in terms of accuracy, specificity, and matthews correlation coefficient. Furthermore, a case study analysis indicates that BoT-Net also outperforms state-of-the-art lncRNA–protein interaction predictor on a benchmark dataset by accuracy of 10%, sensitivity of 19%, specificity of 6%, precision of 14%, and matthews correlation coefficient of 26%. Conclusion In the benchmark lncRNA–miRNA interaction prediction dataset, the length of the lncRNA sequence varies from 213 residues to 22,743 residues and in the benchmark lncRNA–protein interaction prediction dataset, lncRNA sequences vary from 15 residues to 1504 residues. For such highly flexible length sequences, fixed length generation using copy padding introduces a significant level of bias which makes a large number of lncRNA sequences very much identical to each other and eventually derail classifier generalizeability. Empirical evaluation reveals that within 50 residues of only the starting region of long lncRNA sequences, a highly informative distribution for lncRNA–miRNA interaction prediction is contained, a crucial finding exploited by the proposed BoT-Net approach to optimize the lncRNA fixed length generation process. Availability: BoT-Net web server can be accessed at https://sds_genetic_analysis.opendfki.de/lncmiRNA/. Graphic Abstract

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

RETRACTED ARTICLE: Adenosine protects D-galactose induced alterations in rat model of aging via attenuating neurochemical profile and redox status - Noreen Samad; Arooj Nasir; Muhammad Habib ur Rehman; Sheraz Ahmed Bhatti; Imran Imran (Metabolic Brain Disease, 2022)

Quantifying the effect of waste on soil health in European Union: what are the roles of technology, natural capital, and institutional quality? - Muhammad Ibrahim Shah; Abdulrasheed Zakari; Siddharth Kumar; Shujaat Abbas; Muhammad Sheraz (Environmental Science and Pollution Research, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Recent approaches on the optimization of biomass gasification process parameters for product H2 and syngas ratio: a review - Muhammad Zain Siddiqui; Mahshab Sheraz; Umair Ali Toor; Ali Anus; Abid Mahmood; Muhammad Haseeb; Muhammad Ibrahim; Kuan Shiong Khoo; Vishno Vardhan Devadas; Muhammad Mubashir; Sami Ullah; Pau Loke Show (Environment, Development and Sustainability, 2022)

Correction to: Biochemical characterization of Aedes aegypti (Linnaeus) (Diptera: Culicidae) resistance to deltamethrin, fipronil, and imidacloprid - Muhammad Waqas Sumra; Shoaib Freed; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Sikandar Hussain; Afifa Naeem (Environmental Monitoring and Assessment, 2022)

Exploring the dynamic relationship between financial development, renewable energy, and carbon emissions: A new evidence from belt and road countries - Muhammad Sheraz; Xu Deyi; Muhammad Zubair Mumtaz; Atta Ullah (Environmental Science and Pollution Research, 2022)

Bacterial prediction using internet of things (IoT) and machine learning - Hamza Khurshid; Rafia Mumtaz; Noor Alvi; Ayesha Haque; Sadaf Mumtaz; Faisal Shafait; Sheraz Ahmed; Muhammad Imran Malik; Andreas Dengel (Environmental Monitoring and Assessment, 2022)

Inhibitory Effects of Selenium on Arsenic-Induced Anxiety-/Depression-Like Behavior and Memory Impairment - Noreen Samad; Tazeen Rao; Muhammad Habib ur Rehman; Sheraz Ahmed Bhatti; Imran Imran (Biological Trace Element Research, 2022)

A recessive variant in TFAM causes mtDNA depletion associated with primary ovarian insufficiency, seizures, intellectual disability and hearing loss - Farid Ullah; Waqar Rauf; Kamal Khan; Sheraz Khan; Katrina M. Bell; Vanessa Cristina de Oliveira; Muhammad Tariq; Shabnam Bakhshalizadeh; Philippe Touraine; Nicholas Katsanis; Andrew Sinclair; Sijie He; et al. (Human Genetics, 2021)

Biochemical characterization of Aedes aegypti (Linnaeus) (Diptera: Culicidae) resistance to deltamethrin, fipronil, and imidacloprid - Muhammad Waqas Sumra; Shoaib Freed; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Sikandar Hussain; Afifa Naeem (Environmental Monitoring and Assessment, 2021)

Combating immunotoxicity of aflatoxin B1 by dietary carbon supplementation in broiler chickens - Sheraz Ahmed Bhatti; Muhammad Zargham Khan; Muhammad Kashif Saleemi; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2021)

HEC-RAS and GIS-based flood plain mapping: A case study of Narai Drain Peshawar - Awais Salman; Sher Shah Hassan; Gul Daraz Khan; Muhammad Arif Goheer; Aftab Ahmad Khan; Khurram Sheraz (Acta Geophysica, 2021)

Moderating the effect of globalization on financial development, energy consumption, human capital, and carbon emissions: evidence from G20 countries - Muhammad Sheraz; Xu Deyi; Jaleel Ahmed; Saif Ullah; Atta Ullah (Environmental Science and Pollution Research, 2021)

Amelioration of toxicopathological effects of cadmium with silymarin and milk thistle in male Japanese quail (Coturnix japonica) - Muhammad Kashif Saleemi; Muhammad Waseem Tahir; Rao Zahid Abbas; Masood Akhtar; Aamir Ali; Muhammad Tariq Javed; Zahida Fatima; Muhammad Zubair; Sheraz Ahmed Bhatti; Zahoor Ul Hassan (Environmental Science and Pollution Research, 2019)

Effects of feeding bentonite clay upon ochratoxin A–induced immunosuppression in broiler chicks - Aisha Khatoon; Muhammad Zargham Khan; Zain ul Abidin; Sheraz Ahmed Bhatti (Food Additives & Contaminants: Part A, 2018)

Solvent Effect on the Photolysis of Riboflavin - Iqbal Ahmad; Zubair Anwar; Sofia Ahmed; Muhammad Ali Sheraz; Raheela Bano; Ambreen Hafeez (AAPS PharmSciTech, 2015)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Effect of Ascorbic Acid on the Degradation of Cyanocobalamin and Hydroxocobalamin in Aqueous Solution: A Kinetic Study - Iqbal Ahmad; Kiran Qadeer; Saima Zahid; Muhammad Ali Sheraz; Tehmina Ismail; Waqar Hussain; Izhar Ahmad Ansari (AAPS PharmSciTech, 2014)

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications - Iqbal Ahmad; Kiran Qadeer; Kefi Iqbal; Sofia Ahmed; Muhammad Ali Sheraz; Syed Abid Ali; Tania Mirza; Ambreen Hafeez (AAPS PharmSciTech, 2013)

Studies on Tolfenamic Acid–Chitosan Intermolecular Interactions: Effect of pH, Polymer Concentration and Molecular Weight - Sofia Ahmed; Muhammad Ali Sheraz; Ihtesham Ur Rehman (AAPS PharmSciTech, 2013)

Photodegradation and Stabilization of Betamethasone-17 Valerate in Aqueous/Organic Solvents and Topical Formulations - Saif-ur-Rehman Khattak; Dilnawaz Shaikh; Iqbal Ahmad; Khan Usmanghani; Muhammad Ali Sheraz; Sofia Ahmed (AAPS PharmSciTech, 2013)

Photostability and Interaction of Ascorbic Acid in Cream Formulations - Iqbal Ahmad; Muhammad Ali Sheraz; Sofia Ahmed; Riaz Hussain Shaikh; Faiyaz H. M. Vaid; Saif ur Rehman Khattak; Shakeel A. Ansari (AAPS PharmSciTech, 2011)